If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3 = x(1 + x) 0.3 = (1 * x + x * x) 0.3 = (1x + x2) Solving 0.3 = 1x + x2 Solving for variable 'x'. Reorder the terms: 0.3 + -1x + -1x2 = 1x + -1x + x2 + -1x2 Combine like terms: 1x + -1x = 0 0.3 + -1x + -1x2 = 0 + x2 + -1x2 0.3 + -1x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 0.3 + -1x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -0.3 + x + x2 = 0 Move the constant term to the right: Add '0.3' to each side of the equation. -0.3 + x + 0.3 + x2 = 0 + 0.3 Reorder the terms: -0.3 + 0.3 + x + x2 = 0 + 0.3 Combine like terms: -0.3 + 0.3 = 0.0 0.0 + x + x2 = 0 + 0.3 x + x2 = 0 + 0.3 Combine like terms: 0 + 0.3 = 0.3 x + x2 = 0.3 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. + 0.25 + x2 = 0.3 + 0.25 Combine like terms: + 0.25 = 1.25 1.25 + x2 = 0.3 + 0.25 Combine like terms: 0.3 + 0.25 = 0.55 1.25 + x2 = 0.55 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 0.55 Calculate the square root of the right side: 0.741619849 Break this problem into two subproblems by setting (x + 0.5) equal to 0.741619849 and -0.741619849.Subproblem 1
x + 0.5 = 0.741619849 Simplifying x + 0.5 = 0.741619849 Reorder the terms: 0.5 + x = 0.741619849 Solving 0.5 + x = 0.741619849 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 0.741619849 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 0.741619849 + -0.5 x = 0.741619849 + -0.5 Combine like terms: 0.741619849 + -0.5 = 0.241619849 x = 0.241619849 Simplifying x = 0.241619849Subproblem 2
x + 0.5 = -0.741619849 Simplifying x + 0.5 = -0.741619849 Reorder the terms: 0.5 + x = -0.741619849 Solving 0.5 + x = -0.741619849 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -0.741619849 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -0.741619849 + -0.5 x = -0.741619849 + -0.5 Combine like terms: -0.741619849 + -0.5 = -1.241619849 x = -1.241619849 Simplifying x = -1.241619849Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.241619849, -1.241619849}
| 88=2(6p+8) | | -2(y-6)+1=0 | | X(y+5)=66 | | -65=-8x-9 | | 2a^2+8ab=0 | | 2/9*9-4 | | lnx(x^4/4) | | 7a-4a-2a=5 | | 1441/2 | | 5x(x-3)= | | n(3n+2)=0 | | (5x+y)= | | 10p+9-11-p=-4p-8-6p | | 95=25+10*x | | ln(6x+6)=ln(5x+2) | | 3sinx/8 | | 2x+23=3x | | -8+30+-9= | | 11+n=27 | | 6*x-2*x=520 | | x-2*6*x=520 | | sin(x)+5x=0 | | x=5log(x) | | x-2*y=520 | | x*x-9x=-18 | | x-5log(x)=0 | | 9=-3(2b+7) | | 2x^2w^5*8x*2w^4= | | 6x+30=2x+10 | | 2x^2+3x-4=8x-4 | | 3ab*2cd=4ac | | 5(3a-2)=50 |